2020
DOI: 10.1080/19475705.2020.1837967
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal change patterns of vegetation coverage in China and its driving mechanisms over the past 20 years based on the concept of geographic division

Abstract: (2020) Spatial-temporal change patterns of vegetation coverage in China and its driving mechanisms over the past 20 years based on the concept of geographic division,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This study found that vegetation in the growing season has different requirements for temperature and precipitation in different months; therefore, the sensitivity to temperature and precipitation is also different. Studies on the relationship between vegetation cover and climate change in China over the past 20 years have also reached a similar conclusion; that is, the maximum correlation coefficient between vegetation cover and climate factors of different land types is delayed by one month (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
“…This study found that vegetation in the growing season has different requirements for temperature and precipitation in different months; therefore, the sensitivity to temperature and precipitation is also different. Studies on the relationship between vegetation cover and climate change in China over the past 20 years have also reached a similar conclusion; that is, the maximum correlation coefficient between vegetation cover and climate factors of different land types is delayed by one month (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
“…In 1989, Davis first proposed the lag effect of vegetation on climate change (greenhouse warming) [6]. Subsequently, scholars have done a lot of related studies [7][8][9][10]. Wu et al found that regarding the time-lag effects, the climatic factors explained 64% variation of the global vegetation growth, which was 11% relatively higher than the model-ignoring time-lag effects [1].…”
Section: Introductionmentioning
confidence: 99%